Penyusunan IT Balanced Scorecard Untuk Pengukuran Kinerja Pusat SIM Pada Perusahaan Daerah Air Minum (PDAM) Kota Malang - Ameline Devia Mashita Zara; Suprapto Suprapto; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Drinking Water Company (PDAM) of Malang City was a water supply company that applied information technology in carrying out all its activities. Almost all integrated systems and applications between divisions are managed by the center of the Management Information System (SIM) or known as the IT division. Therefore, to increase employee as a user and customer satisfaction with services provided by IT division, PDAM needs performance measurement in IT division to know the contribution of IT division in achieving company's vision and mission. Compiling of IT Balanced Scorecard was an appropriate method to determined how well the performance of IT division in supporting decision making in vision, mission and corporate objectives based on 4 domains. The purpose of the researcher was to developed the target of Key Performance Indicator (KPI) and strategic initiatives for each strategy's target on 4 IT Balanced Scorecard domains. The data itself are collected with interview and observation. From the interview result got 6 strategy's target and 8 KPI for target achievement 3 years ahead. Strategic initiatives gained based on target size are increasing IT costs and user satisfaction with services and improving IT governance and competence of Human Resources (HR) IT division.